THE POWER OF INFORMATION: HOW BUSINESS INTELLIGENCE SHAPES A COMPANY'S ECONOMIC SUSTAINABILITY - Gia Zoidze; Ramaz Otinashvili; Shota Veshapidze (Three Seas Economic Journal, 2025)
Relevance of the topic. Against the background of globalization and the rapid development of information technologies, the role of competitive intelligence in the strategic management of modern business is increasingly increasing. For organizations, general knowledge of the market is no longer enough - to ensure the effectiveness of decisions, an in-depth analysis of both competitors and various elements of the business environment is required. The expansion of the digital space has opened up new opportunities for obtaining information through open sources (OSINT), but at the same time it has also raised new ethical and legal challenges, which makes this topic particularly relevant for modern business practice. Aim and object of the research. The aim of the paper is to evaluate the modern practices of business intelligence, the methods of obtaining information from open and closed sources, their classification and efficiency. The object of the research is the methods used in the competitive intelligence process, their legal and ethical boundaries, as well as their impact on business decisions. Research methods. The paper uses descriptive and analytical research methods. The analysis was carried out based on international literature and expert assessments (e.g. Leonard Fuld's models), as well as practical examples. Information gathering methods are classified according to legality and ethics, which facilitates a comparative analysis of their effectiveness and risks. Practical significance. The paper indicates the need for systematic implementation of business intelligence in both large and medium-sized and small enterprises. The presence of an effective intelligence system not only increases the competitive position of the company, but also reduces strategic and operational risks, improves the speed of adaptation to the market and ensures the achievement of long-term plans. The need for training specialists as part of the national strategy is also emphasized, which will facilitate the legal and ethical use of intelligence tools in the modern Georgian business environment. Results. The study showed that despite the growing importance of open sources (which, according to experts, often provide 95–99% of the information needed for business intelligence), the highest strategic value is often found in semi-closed and difficult-to-access data. At the same time, some methods of information gathering — such as surveys of former employees, test purchases, detailed study of a similar product or pseudo-marketing research — are legal and effective, but on a tight leash in terms of ethical standards.